Native Speaker’s Perception Of The Naturalness In The Japanese Speech Act Response Of Compliment Among Japanese Learners In Indonesia - Bayu Aryanto; Syamsul Hadi; Tatang Hariri (Universitas Diponegoro, 2021)
Responding to compliment sometimes puts the speech partner in a dilemma. Receiving a compliment can cause a chance of a self-compliment impression. If you refuse a compliment, it will give the impression of not appreciating the reasonable judgment of the speech partner (complimenter). This dilemma will be more complicated for foreign language learners, including those who have linguistic skills at an advanced level. This article contains how native speakers provide an assessment for the compliment responses of speeches to Japanese learners, especially in Central Java and D.I.Yogyakarta. Fifty-three respondents were Japanese learners, and five were native Japanese speakers as judges to assess the naturalness of the respondents' compliment speech responses. Among 424 responses of Japanese learners' compliment speech, 55 per cent of the respondents' speech was considered unnatural. It indicates that there has been a socio-pragmatic failure and a pragma-linguistic failure. Socio-pragmatic failure can be seen in the